Arranjo de implementação do projeto Esporte e Cidadania no Estado do Rio de Janeiro: uma parceria do Ministério do Esporte com instituições federais de ensino superior - Samir Jorge Zakur Junior (2021)
The Sport and Citizenship project implemented participatory sport centers in areas of social vulnerability in the state of Rio de Janeiro, serving children and young people from 6 to 21 years old. The general objective of this research is to analyze the implementation of the Sport and Citizenship project in the state of Rio de Janeiro, considering the implementation arrangement of a decentralized execution of sport and leisure policy, in partnership between the Ministry of Sport and federal public universities. To analyze this theme, the study was based on the field of public policies, mainly in the implementation phase, added to the institutional debate on coordination relations between federated entities in the context of decentralization. The study was based on the qualitative case study methodology, and data collection took place through document analysis and semi-structured notes with those responsible for the national coordination and implementation of the project. Results Regarding the scope of the project, the implementation arrangement of the sports ministry with universities, financial with federal emergency resources, made the proposal operational in 44 cities in the state of Rio de Janeiro, implementing 156 sport and leisure centers in should years of project duration. Final considerations. The federal government's partnerships with universities can contribute with their scientific apparatus to the execution of sports and leisure actions. However, the low institutionality of the area creates a fertile field for the execution of projects that seek in the "inaugural actions" to leave the manager's mark, without the commitment to the consolidation of the policy, and, consequently, to the population that acts as a receptacle discredited of temporary proposals for sport and leisure.